Proceedings of the 1st International Conference on Law, Social Science, Economics, and Education, ICLSSEE 2021, March 6th 2021 2021
DOI: 10.4108/eai.6-3-2021.2306482
|View full text |Cite
|
Sign up to set email alerts
|

Level of Individual Performance in the Context of Referencing Competency

Abstract: Referencing competency is the knowledge, skills, and ability to use, edit, and disseminate different types of referencing standards and referencing software. Referencing competency helps to improve the quality of publication through proper citation and references. However, there is a scarcity of knowledge on the level of impact of referencing competency towards individual performance especially among undergraduate students. Therefore, the purpose of this study is to determine the level of individual performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…Students outperformed employees by 18%, while men outperformed women by 26% [56]. This study emphasizes the individual performance of employees and establishes a modest degree of task productivity and satisfaction among respondents in the context of referencing competency [57].…”
Section: Summary On the Level Of Individual Work Performancementioning
confidence: 78%
“…Students outperformed employees by 18%, while men outperformed women by 26% [56]. This study emphasizes the individual performance of employees and establishes a modest degree of task productivity and satisfaction among respondents in the context of referencing competency [57].…”
Section: Summary On the Level Of Individual Work Performancementioning
confidence: 78%
“…Research being conducted by De Marco, Robles and Antino [11] also found that socio-demographic variables influence digital skills. Besides that, students in higher education who are being exposed to some information skills class will have better skills and ability in referencing as they are better in information searching and retrieval [5]. These show that demographic profiles may demonstrate the digital competencies among individuals.…”
Section: Introductionmentioning
confidence: 95%
“…Draganidis and Mentzas [4] defined competencies as direct and indirect skills and behaviours that enable individuals to perform given tasks or assigned roles effectively. Competencies are very important as it is one of the elements that are being used to measure the success of the tasks given [5]. In an academic environment, students are required to have referencing competencies which are skills and knowledge in doing citation or references, to help them from doing plagiarism.…”
Section: Introductionmentioning
confidence: 99%